A aprendizagem ao longo da vida no espaço europeu: proposta de um observatório/ Lifelong learning in the european space: proposal for an observatory - Marques, C.G. (2016)
In this paper, we intend to present the European Observatory on Lifelong Learning (EOLL), a proposal of the National PT Learning Workgroup to identify and monitor lifelong learning initiatives in Europe.